La expresión epigráfica de la divinidad en contextos mágicos del Occidente romano: especificidad, adaptación e innovación - Marco Simón, Francisco (Cahiers du Centre G. Glotz: Revue d'histoire ancienne, 2010)
The spaces of magical rituals make possible a higher degree of spontaneity and individualization that that of the public religion. Having this in mind, this paper aims to analize diverse solutions in the epigraphical expression of divinity in the magical contexts of the western provinces of the Roman empire, from the testament of local deities (such as the Niskae or Adsagonda) unknown in votive altars and dedications, to the consignation of divine personalities kown only in the literary sources, to the integration of elements belonging to a Mediterranean koiné which is mainly defined by the so called Graeco-Egyptian magic and the shift from rituals centered in the temple to other transmitted by travelling specialists (as the turibulum of Chartres, the new defixio of the via Ostiense at Rome or the presence of Abraxas in the sanctuary of Anna Perenna make clear).